LITERATURE REVIEW: USER INTERFACE OF SYSTEM FUNCTIONAL ELECTRICAL STIMULATION (FES) AND ARM ROBOTIC REHABILITATION - Wahyu Abryandoko, Eko; Susmartini, Susy; Widyo Laksono, Pringgo; Herdiman, Lobes (Journal of Applied Engineering Science, 2024)
Interface technology development for human-robot interaction (HRI) in rehabilitation systems has increased in recent years. HRI can effectively achieve specific motor goals desired in rehabilitation, such as combining human intentions and actions with robotic devices to perform the desired stroke rehabilitation movements. Rehabilitation devices are starting to be directed towards using devices that integrate functional electrical stimulation (FES) with robotic arms because they have succeeded in providing promising interventions to restore arm function by intensively activating the muscles of post-stroke patients. However, FES requires a high level of accuracy to position the limbs for the functional tasks given because excessive electrical stimulation can cause fatigue in the patient, so it is necessary to provide electrical stimulation with an amplitude that suits the patient's needs. Unfortunately, most studies have a constant voltage amplitude and do not consider the voltage that matches the patient's muscle needs; this treatment can cause fatigue in the patient. Robotic devices as rehabilitation aids have the potential to support external power and adapt electrical stimulation needs to the voltage amplitude applied to the FES. Integrating FES with a robotic arm support system into one hybrid neuroprosthesis is attractive because the mechanical device can complement muscle action and increase rehabilitation's repeatability and accuracy rate. The integration of FES and robotic arms is a promising approach in the future. This article reviews the state of the art regarding motor rehabilitation using functional electrical stimulation (FES) devices and robotic arms for the upper limbs of post-stroke patients. A narrative review was done through a literature search using the IEEE-Xplore, Scopus, and PubMed databases. Nine different rehabilitation system articles were identified. The selected systems were compared critically by considering the design and actuators, components, technological aspects, and technological challenges that could be developed in the future. This article also examines the development of HRI and emerging research trends in HRI-based rehabilitation.
Keywords: interaksi manusia-robot, arm robot rehabilitasi, FES